2017
DOI: 10.1007/s10653-017-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

A review of global outlook on fluoride contamination in groundwater with prominence on the Pakistan current situation

Abstract: Several million people are exposed to fluoride (F) via drinking water in the world. Current review emphasized the elevated level of fluoride concentrations in the groundwater and associated potential health risk globally with a special focus on Pakistan. Millions of people are deeply dependent on groundwater from different countries of the world encompassing with an elevated level of fluoride. The latest estimates suggest that around 200 million people, from among 25 nations the world over, are under the dread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(36 citation statements)
references
References 103 publications
0
28
0
2
Order By: Relevance
“…Currently, fluorosis is endemic in many areas of Sindh, Balochistan and Punjab, affecting millions of people with a remarkable ratio of children [2]. However, the problem of excessive fluoride in ground water is widespread throughout the world and approximately 200 million individuals among 25 countries are under the terrible providence of fluorosis including India, China, Sri Lanka, Spain, Italy, West Indies and America [3][4][5][6][7]. For example in India alone 21 states out of 29 and 65 million people including 6 million children are affected by fluorosis [8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, fluorosis is endemic in many areas of Sindh, Balochistan and Punjab, affecting millions of people with a remarkable ratio of children [2]. However, the problem of excessive fluoride in ground water is widespread throughout the world and approximately 200 million individuals among 25 countries are under the terrible providence of fluorosis including India, China, Sri Lanka, Spain, Italy, West Indies and America [3][4][5][6][7]. For example in India alone 21 states out of 29 and 65 million people including 6 million children are affected by fluorosis [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For example in India alone 21 states out of 29 and 65 million people including 6 million children are affected by fluorosis [8][9]. In Pakistan, out of 29 major cities 34% had water fluoride greater than 1.5 × 10 6 ng/L including Lahore, Quetta and Tehsil Mailsi with maximum values of 23.6 ×10 6 and 24.48 ×10 6 ng/L, respectively [7]. A large number of human activities increase fluoride in the environment, including chemical production plants, waste pools, production of aluminum, steel, glass, enamel, brick, tile, pottery, and cement, manufacture of fluoride containing chemicals, phosphate fertilizers and metal casting, welding, and brazing [10] In 2002, a study reported in India showed fluorosis in 10% of children, even when the concentration of fluoride in water was 1.0 ×10 6 ng/L [11].…”
Section: Introductionmentioning
confidence: 99%
“…La fluorose dentaire est, comme la MIH, une pathologie du développement de l'émail, qui, comme cette dernière, provoque des tâches opaques blanchâtres à brunâtres, ce qui peut, dans certains cas, poser des problèmes de diagnostic entre les deux pathologies. La fluorose touche moins de 3 % des enfants en France, mais près de 200 millions de personnes dans le monde, réparties dans 25 pays [32]. La dose de fluor prophylactique est évaluée à 0,05 mg/ kg/j.…”
Section: Le Fluor : Des Effets Bénéfiques Et Des Effets Secondairesunclassified
“…Sin embargo, también se debe considerar que estos cambios pueden ser respuesta de la gran influencia que tiene la evaporación e infiltración en las concentraciones de F en las regiones áridas de México y en otras partes del mundo (Rasool et al, 2017).…”
Section: Distribución Espacial De Los Niveles Deunclassified